Expanding Nonresidential Property Tax Bases for School Finance in New York State: Implications for Student Equity - Brian O. Brent (Journal of Research in Rural Education, 1998)
This study examines the efficacy ofnonresidential expanded tax base approaches (ETB) to school finance. In general, nonresidential ETB approaches permit districts to maintain taxing authority over their residential property, while removing nonresidential property from the local tax base. The pool ofnonresidential property is instead taxed at the state or regional level, with the proceeds distributed back to local districts in some equalizing manner. The study includes a simulation that estimates the effects ofstatewide and regional nonresidential ETB approaches on measures ofstudent equity for New York school districts in 1990-1991. Findings suggest that expanded tax base approaches are promising and need not have adverse effects on urban areas. In particular, the study's findings suggest that (a) nonresidential ETB approaches improve measures ofstudent equity at no additional cost to the state (i.e., state aid), (b) that regional in contrast to statewide ETB approaches work to the advantage of urban areas in the state, and (c) the manner in which pooled nonresidential property tax revenues are distributed to local districts is a critical determinant of the policy's ability to improve measures of equity.